LEGAL RESPONSIBILITY OF MARKETPLACES FOR ILLEGAL PRODUCTS: A COMPARATIVE STUDY BETWEEN INDONESIA AND THE EUROPEAN UNION - Jenda Ingan Mahuli (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Advances in information technology have driven the digital transformation of trade through the presence of marketplaces, namely online platforms that facilitate interactions between sellers and buyers without geographical boundaries. However, along with this growth, serious legal challenges have also emerged, namely the increasing circulation of illegal products such as cosmetics without distribution permits, pirated goods, and illegal drugs. This problem raises questions about the legal responsibility of marketplaces for the circulation of illegal products sold by third parties through their platforms. This study aims to analyze and compare the regulation of marketplace legal responsibility for illegal products in Indonesia and the European Union. This study uses a normative method with a legislative approach and a comparative approach. The results of the study show that regulations in Indonesia, such as PP No. 80 of 2019 and Law No. 8 of 1999 concerning Consumer Protection, still positions marketplaces as passive electronic system organizers who do not have full responsibility for the legality of products. This results in weak legal protection for consumers. In contrast, the European Union through the Digital Services Act (2022) has established active responsibility for marketplaces, including the obligation to Know Your Business Customer (KYBC), a notice and action system, and administrative sanctions for violations. According to Cauffman (2022), “The Digital Services Act transforms online platforms from neutral facilitators to duty bearers with concrete responsibilities.” This study concludes that Indonesia needs to reform e-commerce regulations by adopting stronger consumer protection principles as implemented in the European Union. The main recommendation of this study is the establishment of specific regulations that explicitly stipulate the legal responsibility of marketplaces for the circulation of illegal products in the digital space.